Comparison of Muscle Thickness and Changing Ratio for Cervical Flexor Muscles During the Craniocervical Flexion Test Between Subjects With and Without Forward Head Posture - Jae-hyun Lee; Ui-jae Hwang; Oh-yun Kwon (Korean Research Society of Physical Therapy, 2022)
Background: The craniocervical flexion test (CCFT) was developed for the activation and en-durance of deep cervical flexors. However, the muscle thickness and muscle thickness chang-ing ratio of the sternocleidomastoid (SCM) and deep cervical flexor (DCF) muscles in subjects with and without forward head posture (FHP) have not been reported.Objects: To determine the difference in thickness of the SCM and DCF muscles and the differ-ence in the muscle thickness changing ratio between SCM, DCF, and DCF/SCM 20 mmHg and DCF/SCM 30 mmHg between subjects with and without FHP.Methods: Thirty subjects with and without FHP were enrolled. The muscle thickness of the SCM and DCF was measured when maintained at a baseline pressure of 20 mmHg and a maxi-mum pressure of 30 mmHg using a pressure biofeedback unit during the CCFT. Ultrasonog-raphy was used to capture images of SCM and DCF muscle thickness during the CCFT, which was calculated using the picture archiving and communication system (PACS). Results: We observed a significant difference within the pressure main effect between SCM and DCF at a baseline pressure of 20 mmHg and a maximum pressure of 30 mmHg (p < 0.05). However, there was no significant difference in the muscle thickness and muscle thickness changing ratio for SCM and DCF during CCFT between subjects with and without FHP.Conclusion: There was no significant difference in the muscle thickness recruitment pattern during CCFT in posture changes between subjects with and without FHP.